2009
DOI: 10.1148/radiol.2503080874
|View full text |Cite
|
Sign up to set email alerts
|

Myometrial Invasion in Endometrial Cancer: Diagnostic Accuracy of Diffusion-weighted 3.0-T MR Imaging—Initial Experience

Abstract: Fused T2-weighted and high-b-value DW images at 3 T can provide accurate information for preoperative evaluation of myometrial invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
91
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(111 citation statements)
references
References 22 publications
15
91
4
1
Order By: Relevance
“…WbT2/wbDWI image fusion shows significantly higher detection rates compared with wbT2 and wbDWI alone, which parallels findings from retrospective image fusion studies of DWI and T2-weighted image data [31][32][33]. However, these studies did not evaluate side-by-side analysis.…”
Section: Discussionsupporting
confidence: 60%
“…WbT2/wbDWI image fusion shows significantly higher detection rates compared with wbT2 and wbDWI alone, which parallels findings from retrospective image fusion studies of DWI and T2-weighted image data [31][32][33]. However, these studies did not evaluate side-by-side analysis.…”
Section: Discussionsupporting
confidence: 60%
“…3 Das SK et al in their meta-analysis of usefulness of DWI in endometrial cancer patients found sensitivity and specificity for detection of deep myometrial invasion to be 90% and 89% respectively. 4 They concluded that DWI offered potential advantages over Dynamic Contrast enhanced MRI as it did not involve use of intravenous contrast which would be contraindicated in patients with renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…MRI, has allowed correct evaluation of myometrial invasion in cases complicated by adenomyosis and other factors that make the evaluation dif cult 28 .…”
Section: Discussionmentioning
confidence: 99%